Aquatic Wildmeat Consumption of Guiana Dolphins (Sotalia guianensis) in Lake Maracaibo System, Venezuela - Briceño, Yurasi; Sánchez, Leonardo; Trujillo, Fernando; von Fersen, Lorenzo; Ramírez, Sonsireé (Frontiers in Marine Science, 2021)
In many regions of the world, the use of cetaceans as bait or protein source has been reported. In most cases the individuals are from bycatch but also from intentionally killed animals. Cetaceans with coastal habits are more susceptible to negative interactions with small-scale fisheries, as in the case of the Guiana dolphin (Sotalia guianensis) in the Lake Maracaibo system. For decades, the use of Guiana dolphins by local communities has been reported in this region and is culturally supported by recipes for its preparation. Most of these data was outdated and some were anecdotal, so the objective of this work was to collect systematically data through surveys using the snowball method in seven artisanal fishing communities and to try to quantify the capture rate and to inquire about the potential impact of this practice on the population of Guiana dolphin. From 2017 to 2019, 95 semi-structured interviews were applied. An average bycatch of 180 individuals / year was obtained, the highest catch rate in the entire geographic distribution, an alarming situation considering that the surveys were not carried out in all the fishing ports, generating an underestimation. A total of 78 % of interviewed recognized at least one bycatch event during their fishing effort. Surveys revealed a higher incidence of entanglement of offspring and juveniles (78%). 77% of the respondents deny the sale and commercialization of the species, while 5% mention some type of trade. The most frequent part exploited was the dorsal muscle, confirmed by fishermen (97%, n = 72) and the rest of the animal is discarded. During this investigation three episodes of directed capture were recorded, affecting a total of 23 individuals, two of them were pregnant females. The interviews also revealed that the majority of fishermen (93%) recognize the capture of this species as illegal. Considering the vulnerability of the Guiana dolphin in the country, the high incidence of capture and consumption and the lack of surveillance and sanctions by government entities, it is imperative to immediate actions to mitigate the negative impact on the population.